Les identités de la ville : Éléments analytiques pour une étude sociolinguistique - Souheila HEDID (Lengas)
The following study is part of a scientific project which aims to highlight the different configurations / reconfigurations of the sociolinguistic context of the city of Constantine (in Algeria) after the multiple development operations of the territory (carried out as part of the rehabilitation of the old city, where entire cities were moved to a new city "Ali Mendjeli"). It is based on a plural qualitative methodology where several investigative tools are used with an experimental approach and field surveys that affect the whole city.This work questions an important aspect of this circuit, that of the social integration of new housing sites. This problem constitutes a very important line of study in sociology because it is at the center of a very great questioning that of the socialization of individuals in any social environment. Our purpose is to show that the integration of a space is a complex experience because it calls for a multiform adaptation, as well social, psychological as linguistic….